Phyllosphere Bacteria Improve Animal Contribution to Plant Nutrition - Goncalves, Ana Z.; Hoffmann, Fernando L. [UNESP]; Mercier, Helenice; Mazzafera, Paulo; Romero, Gustavo Q. (Wiley-Blackwell, 2014)
Many plant species have evolved special adaptations for acquiring nitrogen in nutrient-poor soils. In Brazilian savannas, the bromeliad Bromelia balansae (Bromeliaceae) is inhabited by mutualistic spiders (Psecas chapoda, Salticidae), which provide nutrients to the plant through their debris (feces, prey carcasses). In this study, we tested if bacteria present on the B. balansae phyllosphere improves plant nutrition and growth by mineralizing complex organic N compounds from spider debris that accumulate on the phyllosphere into simple compounds that may be absorbed easily by leaves. We conducted a greenhouse experiment by manipulating bacteria abundance on the bromeliad phyllosphere using antibiotics. Using isotopic mixed model equations, we demonstrated that debris from spiders contributed 10.71.9 percent (mean +/- standard error) of the N in bromeliads that had their bacterial abundance reduced. In contrast, spider feces contributed 27.1 +/- 4.4 percent of bromeliad N in the presence of the entire bacterial assemblage. These bromeliads accumulated 57 percent more soluble protein and grew 13 percent more than bromeliads that were grown under reduced bacterial density. These results highlight the importance of mineralizing bacteria on phyllosphere as a mechanism of N uptake by bromeliads.
Keywords: bacteria; bromeliads; nitrogen flux; phyllosphere; savanna; soluble protein